Behavior Change Communication Implemented at Scale in Nigeria Increases the Prevalence of Key Infant and Young Child Feeding Practices. (14th June 2022) - Flax, Valerie; Fagbemi, Mariam; Schnefke, Courtney; Kawu, Auwalu; Edwards, Susan; Unangst, Jennifer; Bose, Sujata
Abstract: Objectives: The objective of this study was to evaluate the impact of Alive & Thrive Nigeria's infant and young child feeding (IYCF) behavior change communication (BCC) activities, including interpersonal communication in health facilities, community mobilization, and mass media, on early initiation of breastfeeding, exclusive breastfeeding, and minimum dietary diversity. Methods: Local government areas in Kaduna and Lagos States were randomized to intervention or comparison and cross-sectional surveys of households with children aged 0–23 months [N = 6, 266 baseline (2017), N = 7, 320 endline (2020)] were conducted. Difference-in-differences and post-hoc baseline-endline models were used to measure intervention impacts. Results: Difference-in-differences models showed no significant differences between the intervention and comparison areas in early initiation of breastfeeding (both states), exclusive breastfeeding (Kaduna), or minimum dietary diversity (both states). In Lagos, an 11.5 percentage point increase in exclusive breastfeeding in the intervention compared with the comparison area trended toward significance (P = 0.08). At endline, exposure to interpersonal communication, community mobilization, and mass media did not differ by study area in either state. Given the overall lack of differences in intervention exposure by study area, post-hoc baseline-endline analyses were performed with the study areas combined and increases were detected in early initiation of breastfeeding (Kaduna 40% to 46%, P = 0.05), exclusive breastfeeding (Kaduna 25% to 43%, P < 0.001), and minimum dietary diversity (Kaduna 20% to 41%, P < 0.001; Lagos 37% to 58%, P < 0.001). Conclusions: This evaluation found minimal impacts of the Alive & Thrive intervention on IYCF practices in the difference-in-differences analysis because of intervention spillover to the comparison area. Increases in IYCF practices from baseline to endline were substantial and are likely attributable to the intervention, which was the major IYCF promotion activity in both states. Funding Sources: This research was funded by the Alive & Thrive initiative, managed by FHI Solutions, and currently funded by the Bill & Melinda Gates Foundation, Irish Aid, the Tanoto Foundation, UNICEF, and the World Bank.